Lernziel Demokratie : politische Frauenbildung in der britischen und amerikanischen Besatzungszone 1945 - 1949 - Ziegler, Christl (Studien zur internationalen Erwachsenenbildung;, 1997)
Deals with the British and American efforts for re-education of German women, post World War II, to encourage a greater feminine involvement in German politics.